Dystopia in the Skies: Negotiating Justice and Morality on Screen in the Video Game BioShock Infinite - Stefan Schubert (European Journal of American Studies)
In this article, I analyze the 2013 video game BioShock Infinite as a popular site for the visual display of (in)justice and (im)morality. I contend that it is not so much the game’s ludic elements but its visuality that most forcefully makes a compelling argument against the oppression and discrimination found in the game’s fictional world, the city of Columbia. The game’s visual elements—as part of its larger plot, its narrative background, and the way history is depicted—particularly work to highlight racial and social injustice at the core of Columbia’s society. In turn, the game suggests to draw parallels between these fictional representations and actual US society at the beginning of the twentieth century.